Determination of Selection Index of Cocoa (Theobroma cacao L.) Yield Traits Using Regression Methods - Bayu Setyawan; Taryono .; Suyadi Mitrowihardjo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
The increasing chocolate consumption has not been followed by growing production of dry cocoa beans. In order to support the increase in cocoa production, planting materials with high yield are needed. The objective of this research was to determine the components of cocoa traits affecting weight of dry cocoa beans, and set a selection index for superior cocoa trees. The experiment material were four cocoa hybrid populations of which their family ancestry were unknown, and were planted on Samigaluh Plantation, Yogyakarta, and Segayung Plantation, Central Java. Observations and data collection were conducted on four plant populations. The observations were undertaken for three years, by observing plant traits, including pod length, pod diameter, husk thickness, cavity diameter, pod fresh weight, cocoa bean/pod fresh weight, husk fresh weight, dry weight of cocoa beans/pod, number of cocoa beans/pod, dry weight per cocoa bean. The collected data were analyzed using path and regression analysis methods. The results showed that pod diameter (X4), fresh pod weight (X5), number of cocoa beans/pod (X8), and dry weight/cocoa bean (X9) were used to form a selection index resulting the equation I = 0.0792 X4 + 0.1330 X5 + 0.0106 X8 + 0.1349 X9 furthermore will be used in the selection of cocoa trees. Ten cocoa plants from seeds having the highest general selection index were D 034, D 003, D 015, A 054, D 004, D 033, D 041, A 157, D 036, and D 025 will be selected for further evaluation.